PENYULUHAN EVAKUASI MANUAL UNTUK KESIAPSIAGAAN PADA KONDISI KEBAKARAN DI KELURAHAN KAMAL SUKOHARJO - Gatot Suparmanto; Nurul Devi A; Linda Lidyana (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
Evacuation of victims is an activity of moving victims from the scene of the incident to a safe place, so that in the end the victim gets further treatment and treatment. Preparedness can also be defined as a state of readiness in the face of a crisis, disaster or other emergency. Preparedness aims to minimize the side effects of hazards through effective, timely, adequate, and efficient preventive measures for emergency response actions and assistance during disasters. The method used is a simulation method of self-evacuation for residents. The purpose of this counseling is to train residents so that residents understand how to self-evacuate in a fire condition. The results were obtained before the simulation was carried out, a pre-test was carried out for 30 residents, the average result was 56, which means low and after the simulation and post-test were given, the score became 86, which means good for community preparedness. used to improve the preparedness